Benefits of Friction. Inner[Out]Side Identities - Frühwirth, Angelika; Mijić, Ana (Momentum Quarterly, 2018)
Whoever wants to stay, has to adapt; whoever wants to approach someone, has to match specific ideals; whoever wants to live, has to function. Based on those claims of a rigidified reality identified in the novels of three Viennese authors with “Yugoslavian” backgrounds, this paper pursues the question of how self-images in such reified/rigid systems are forged and how much space for individual liberties still remains. The literary analysis of the novels is contrasted with a hermeneutical interpretation of interviews that have been conducted with individuals who have experienced migration. The contrasting juxtaposition shows that basic analogies can be identified between the ways the protagonists of the novels deal with rigidified realities and the strategies for shaping diasporic identities detected in the interviews: assimilation, overcompensation, rigidification or resignation can be identified in both the novels and the interviews. Occasionally, however, moments of resistance also become manifest in the material. By deliberately generating friction, the characters in the novels and interviewees positioned in the inner[out]side regain control over their own identity.